2020
DOI: 10.1136/bjsports-2019-100989
|View full text |Cite
|
Sign up to set email alerts
|

Habitual physical activity, renal function and chronic kidney disease: a cohort study of nearly 200 000 adults

Abstract: BackgroundThere is limited information on the association between habitual physical activity (PA) and renal function.ObjectiveTo report the longitudinal association between self-reported habitual PA and measures of renal function in a large cohort in Taiwan.MethodsA total of 199 421 participants (aged ≥20 years) were selected from a Taiwan cohort between 1996 and 2014. All participants underwent at least two standardised medical examinations between 1996 and 2014. Self-administrated questionnaires were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 43 publications
5
42
1
1
Order By: Relevance
“…The nding in this study of no signi cant association between leisure-time physical activity and incident CKD agrees with other studies in Australia [10] and the United States [11,28] For example, the AusDiab Study of 6,318 Australian adults showed that inactive (0 min/week) and insu ciently active (< 150 min/week) leisure were not associated with a higher risk of CKD onset compared to su ciently active (≥ 150 min/week) [10]. By contrast, a more recent Taiwanese cohort study among 190,074 adults [13] reported a signi cant, albeit modest, reduction in CKD incident associated with leisure-time physical activity; compared to workers with very low leisure-time physical activity, HRs for low, moderate, and high leisure-time physical activity were 0.93 (95%CI 0.88-0.98), 0.94 (95%CI 0.89-0.99), and 0.91 (95%CI 0.85-0.96), respectively. Given this small size of risk reduction and no clear dose-response relationship in the Taiwanese cohort, together with no association in other prospective studies, the epidemiological evidence has not supported a signi cant protective role of leisure-time physical activity against CKD.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The nding in this study of no signi cant association between leisure-time physical activity and incident CKD agrees with other studies in Australia [10] and the United States [11,28] For example, the AusDiab Study of 6,318 Australian adults showed that inactive (0 min/week) and insu ciently active (< 150 min/week) leisure were not associated with a higher risk of CKD onset compared to su ciently active (≥ 150 min/week) [10]. By contrast, a more recent Taiwanese cohort study among 190,074 adults [13] reported a signi cant, albeit modest, reduction in CKD incident associated with leisure-time physical activity; compared to workers with very low leisure-time physical activity, HRs for low, moderate, and high leisure-time physical activity were 0.93 (95%CI 0.88-0.98), 0.94 (95%CI 0.89-0.99), and 0.91 (95%CI 0.85-0.96), respectively. Given this small size of risk reduction and no clear dose-response relationship in the Taiwanese cohort, together with no association in other prospective studies, the epidemiological evidence has not supported a signi cant protective role of leisure-time physical activity against CKD.…”
Section: Discussionsupporting
confidence: 84%
“…Physical activity is another important factor known to reduce cardiovascular risk [6] and is hypothesized to be an important modi able risk factor in the development of CKD, either directly or indirectly through favorable effects on diabetes, hypertension, and obesity [7,8]. Although physical inactivity has been reported as a risk factor of CKD in several cross-sectional studies [9][10][11][12], evidence from prospective studies has been limited and inconsistent [10,11,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies suggest a two-way relationship between constipation and CKD. On the one hand, the presence of constipation is independently associated with a higher risk of developing CKD and end-stage renal disease (ESRD); it is hypothesized that these relationships can be mediated by an altered gut microbiota and/or be a result of common cause such as lack of regular physical activity 11 - 13 . On the other hand, CKD since its moderate stage (i.e.…”
Section: Introductionmentioning
confidence: 99%